Low-Density Lipoprotein Receptor-Related Protein 1 (LRP1) Is a Negative Regulator of Oligodendrocyte Progenitor Cell Differentiation in the Adult Mouse Brain - Auderset, Loic; Pitman, Kimberley A.; Cullen, Carlie L.; Pepper, Renee E.; Taylor, Bruce V.; Foa, Lisa; Young, Kaylene M. (Frontiers in Cell and Developmental Biology, 2020)
Low-density lipoprotein receptor-related protein 1 (LRP1) is a large, endocytic cell surface receptor that is highly expressed by oligodendrocyte progenitor cells (OPCs), and LRP1 expression is rapidly downregulated as OPCs differentiate into oligodendrocytes (OLs). We report that the conditional deletion of Lrp1 from adult mouse OPCs (Pdgfr-CreER :: Lrp1fl/fl) increases the number of newborn, mature myelinating OLs added to corpus callosum and motor cortex. As these additional OLs extend a normal number of internodes, that are of a normal length, Lrp1-deletion increases adult myelination. OPC proliferation is also elevated following Lrp1 deletion in vivo, however, this may be a secondary, homeostatic response to increased OPC differentiation, as our in vitro experiments show that LRP1 is a direct negative regulator of OPC differentiation, not proliferation. Deleting Lrp1 from adult OPCs also increases the number of newborn mature OLs added to the corpus callosum in response to cuprizone-induced demyelination. These data suggest that the selective blockade of LRP1 function on adult OPCs may enhance myelin repair in demyelinating diseases, such as multiple sclerosis.